(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
To assess the potential and capability of different MPI scanner designs and architectures, defined reference phantoms for imaging studies are required. For the preparation of well-defined structures as well as realistic vessel structures, 3D printed molds were filled with magnetic nanoparticles embedded into a long term stable polymeric matrix or perfused with a flowing ferrofluid. Different types and layouts of 3D printed phantoms will be presented which were imaged by means of MPI successfully.